T4 Calcium-sensing receptor antagonists (calcilytics) as a novel therapeutic for alarmin-driven inflammatory lung disease. (12th November 2019) - Mansfield, B; Huang, P; Bruce, R; Ho, T-R; Du, X; Huang, Q; Wang, W; Lugg, ST; Ford, W; Kidd, E; Corrigan, C; Ward, JPT; et al.
Abstract : Introduction: Exposure to urban particulate matter (UPM) exacerbates the development of asthma and COPD. UPM exposure triggers the release of 'alarmins' by the airway epithelium, which causes an inflammatory response such as acceleration of the activation and maturation of dendritic cells (DC). Previously, we have demonstrated that, in surrogate models of allergic asthma, certain environmental stimuli activate the airway calcium-sensing receptor (CaSR), which drives bronchial hyperresponsiveness, inflammation and remodelling. We have also shown that CaSR antagonists, calcilytics, can abrogate these changes. Whether UPM exerts its effects acting at the CaSR is unknown. Aims: To test the ability of calcilytics to: Prevent the effects of UPM in recombinant systems expressing the CaSR and in DC; Suppress airways hyperresponsiveness, inflammation and remodelling in a murine model of alarmin–driven (IL–33) asthma. Methods: [Ca 2+ ]i responses to UPM were investigated in HEK293 cells stably transfected with human CaSR (HEK-CaSR) or empty vector (HEK-0), ± calcilytic NPS2143. FACS and cytometric bead array were used to evaluate maturation (%CD83) and cytokine release by human monocyte-derived DC following 24h exposure to UPM ± calcilytics. IL-33 was delivered intranasally to naïve mice once daily for 6 consecutive days followed by the calcilytic NPSP795 or vehicle control twice daily from day 2. On day 7, airways resistance was measured (Flexivent) under terminal anaesthesia, after which bronchoalveolar lavage fluid (BALF) analysis was performed, and lungs collected for histomorphology and for measurements of cytokine release. Results: UPM increased [Ca 2+ ]i in the HEK-CaSR but not the HEK-0 cells, an effect inhibited by calcilytics. Calcilytics attenuated UPM-induced maturation, and release of the cytokines IL-10 and IL-23p40, but not IL-6 by DC. In vivo, inhaled calcilytics significantly reduced (1) bronchial hyperresponsiveness; (2) BALF inflammatory cell infiltration and lung concentrations of IL-5, IL-13 and IL-6; (3) airways collagen deposition. Conclusions: UPM activates the CaSR and induces maturation and activation of DC, an effect inhibited by calcilytics. Furthermore, calcilytics show benefit in alarmin-driven airways inflammation and hyperresponsiveness in an animal asthma surrogate, suggesting that they will be effective against exacerbating stimuli such as UPM.